2009
DOI: 10.1371/journal.pone.0008414
|View full text |Cite
|
Sign up to set email alerts
|

JNK1 Phosphorylates SIRT1 and Promotes Its Enzymatic Activity

Abstract: SIRT1 is a NAD-dependent deacetylase that regulates a variety of pathways including the stress protection pathway. SIRT1 deacetylates a number of protein substrates, including histones, FOXOs, PGC-1α, and p53, leading to cellular protection. We identified a functional interaction between cJUN N-terminal kinase (JNK1) and SIRT1 by coimmunoprecipitation of endogenous proteins. The interaction between JNK1 and SIRT1 was identified under conditions of oxidative stress and required activation of JNK1 via phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
162
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(183 citation statements)
references
References 24 publications
(31 reference statements)
10
162
7
1
Order By: Relevance
“…Serine 47 in SIRT1 has been shown to be target of JNK1 (21). Furthermore, Gao et al (18) recently showed that JNK1 leads to SIRT1 phosphorylation and a fast increase in SIRT1 activity upon glucose treatment that correlates very well with the time course that we observed for PKA-dependent SIRT1 activation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Serine 47 in SIRT1 has been shown to be target of JNK1 (21). Furthermore, Gao et al (18) recently showed that JNK1 leads to SIRT1 phosphorylation and a fast increase in SIRT1 activity upon glucose treatment that correlates very well with the time course that we observed for PKA-dependent SIRT1 activation.…”
Section: Discussionsupporting
confidence: 87%
“…In this regard, it has been described that SUMOylation (17) and phosphorylation by several kinases (18 -23) can increase SIRT1 activity. The kinases cyclin-dependent kinase 1 (22), casein kinase, (23,24), and the c-Jun N-terminal kinase (JNK) (21) have been shown to directly phosphorylate SIRT1. On the other hand, it has been reported that the cAMP-dependent protein kinase (PKA) activates SIRT1 indirectly (19), the effects being mediated by an unidentified kinase.…”
mentioning
confidence: 99%
“…Further work is required to determine the mechanism by which SIRT1 negatively regulates JNK activation, however, our findings shed further light on the anti-apoptotic function of SIRT1 activation. Disagreeing results have been obtained by Nasrin and coworkers, who found that JNK1 modifies the function of SIRT1, stimulating its activity and altering its localization [68]. Indeed, our data on the whole suggest an important role for JNK in IR-induced cell death and for SIRT1 in JNK inhibition.…”
Section: Discussionsupporting
confidence: 67%
“…However, the combined treatment of RSV and CCA resulted in the most prominent translocation and colocalization of SirT1 and PGC-1␣ to the nucleus. These data support a mechanism for SirT1 to directly influence PGC-1␣ cotranscriptional activity within the nucleus (34), an effect that may be mediated by ROS, signaling molecules elevated during exercise (38).…”
Section: Rsv Induces Ampk and P38 Activity In A Temporal Manner That supporting
confidence: 75%